PENERAPAN SIX SIGMA DALAM MEMINIMASI CACAT PRODUK SOUVENIR PADA HOME INDUSTRI MATA KAYU ART - Dedi Dermawan; Sri Lestari; Faradila Ananda Yul (Jurnal Teknik Industri Terintegrasi, 2021)
Mata Kayu Art is a center for selling unique souvenirs and furniture, its superior products made of pine wood are placards, sitting clocks, wall clocks, and so on. Home Industry Mata Kayu Art was established in mid-2018, which is located on Jl. Karya, district. Panam, Pekanbaru City. The purpose of this study is to identify the number of defective products and measure the level of sigma and determine the factors that cause defective products so that they can provide suggestions for improvements to the company by redesigning SOPs to reduce defects or defects. The method used is the Six Sigma method, with the steps of Define, Measure, Analyze, Improve, and Control (DMAIC). Based on the calculation results that in the souvenir production process two types of defects become Critical to Quality (CTQ), namely broken and cracked, while souvenir products that often experience defects are Plaque products, Key Chain products, and Sitting Clock products which are then obtained Defect values. per Million Opportunity (DPMO) obtained for Broken defects is 11029 and for Cracked defects is 3676 while the sigma value obtained for Broken defects is 3.79 and for Cracked defects is 4.18. The company strives to be able to implement six sigma with the Define, Measure, Analyze, Improve, and Control (DMAIC) stages to improve quality with the hope that there will be no defects or zero defects. Keywords: Defect; DMAIC; DPMO; Six Sigma.